Condicions prosòdiques i minimitat en el tipus reduplicatiu «puput» - Cabré Monné, Teresa (Caplletra. Revista Internacional de Filologia, 1995)
The purpose of this paper is to give a description of one of the Catalan reduplication processes: the reduplication of one light syllable at the left edge of the word. This process exhibits some prosodic conditions in the output as well as in the input. The input must be one heavy syllable, and the output cannot exceed two syllables. Both are subject to Minimality: base words contain minimally one foot, reduplicative words contain maximally one foot. The reduplicative template is a light syllable, its segmental melody being mapped from the base. The description of this process provides evidence for a templatic approach within Prosodic Morphology.